(untitled) (Eurasian Research Bulletin, 2025)
This article considers a nonlocal problem for a fourth-order equation in a quadrilateral domain. Using the Galerkin method, the existence and uniqueness of a generalized soliton in a Sobolev space is proven under certain conditions on the coefficients and the righthand side of the equation